2019
DOI: 10.1002/adsc.201900485
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Fluoride and Copper‐Catalyzed One‐Pot Synthesis of Benzoxazoles via a Site‐Selective Amide C−N Bond Cleavage

Abstract: We report herein a two-step one-pot strategy for the synthesis of benzoxazoles from amides by using cesium fluoride/copper as catalysts. This approach involves the in situ generation of acyl fluorides from the corresponding amides, and the acyl fluorides undergo transamidation and cyclization to give benzoxazoles in good yields. In this work, the amide CÀ N bonds are activated by CsF to form the acyl fluoride intermediates, which further react with o-bromoanilines to efficiently yield benzoxazoles. Notably, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Some starting materials of amides were synthesized according to corresponding literature . Citations to the references containing characterization data for these compounds are given: 1a , 1b , 1c , 1d , 1f , 1i , 1k , 1n , 1o , 1p , 1a – a , 1a – c , 1a – d , 1a – e , 1a – f , 1a – g , 1a – h , 1a – i , 1a – j , 1a – k , 1a – l , 1a – m , 4a , 4d , 4c , 4f , and 4g …”
Section: Methodsmentioning
confidence: 99%
“…Some starting materials of amides were synthesized according to corresponding literature . Citations to the references containing characterization data for these compounds are given: 1a , 1b , 1c , 1d , 1f , 1i , 1k , 1n , 1o , 1p , 1a – a , 1a – c , 1a – d , 1a – e , 1a – f , 1a – g , 1a – h , 1a – i , 1a – j , 1a – k , 1a – l , 1a – m , 4a , 4d , 4c , 4f , and 4g …”
Section: Methodsmentioning
confidence: 99%
“…In 2018, the Zeng group applied their CsF-catalyzed transamidation to the synthesis of benzoxazoles via onepot, two-step tandem process involving CsF-catalyzed siteselective N-C(O) bond cleavage and Cu-catalyzed intramolecular cyclization (Scheme 28). 55 In this method, N,N-Boc 2activated 1° amides or N-Ts-activated 2° amides were treated with CsF and 2-haloanilines to afford transamidation products, which were then converted into benzoxazoles via intramolecular cyclization in the presence of Cu(I) catalysis. This method tolerates various amide and aniline substrates, affording benzoxazoles in good to excellent yields.…”
Section: Scheme 27 Transition-metal-free Transamidation Of Primary Ammentioning
confidence: 99%
“…Szostak, 40–57 Garg, 58–68 Zou, 69–71 Yamaguchi, 72–76 Huang, 77–83 Shi, 84–86 and Rueping 87–89 have made great contributions to the study of amide transformation. Our group 90–105 has also conducted excellent research in this field. As a thiocarbonyl analog of amide, it is extremely rarely reported that activated thioamide C–N bond cleavage formed various thio-compounds.…”
Section: Introductionmentioning
confidence: 99%